Environmental sustainability measurement in the Travel and Tourism Competitiveness Index: an empirical analysis of its reliability - Dias, J. G. (Ecological Indicators, 2017)
Indices provide a straightforward summary of the status of an object or concept. Examples of concepts are diverse and go from city quality of life, country level of freedom, human development to environment sustainability. This paper introduces a methodology to assess the reliability of the environmental sustainability index implemented by the Travel and Tourism Competitiveness Index that is published by the World Economic Forum using exploratory and confirmatory factor analyses. Results show that the original index is not reliable as most of the variables are weakly correlated. A simplified version of the original index is obtained by exploratory factor analysis and tested by confirmatory factor analysis. Measures of reliability show that the new index called TTESI – Travel & Tourism Environmental Sustainability Index – is reliable. Results also show that combining data from different sources (e.g., survey data and physical measurements) proves problematic. A z-score value for each country was computed and countries were ranked based on the TTESI. Additionally, the new index is more in line with the HDI – Human Development Index – and can therefore be integrated more easily in an overall index of sustainable development.